ДОТАЦІЇ У ЗАБЕЗПЕЧЕННІ ФІНАНСОВОГО ПОТЕНЦІАЛУ ТЕРИТОРІЙ (Світ фінансів, 2018)
Письменний В. В. Дотації у забезпеченні фінансового потенціалу територій.Проаналізовано сучасний стан і проблеми функціонування дотацій у доходах місцевих бюджетів України. Теоретично вони є ефективним методом бюджетного регулювання, який дає змогу вилучити фіксовану суму коштів із бюджету вищого рівня для збалансування бюджету нижчого рівня в разі перевищення видатків останнього над його доходами. Встановлено, що в Україні через корупцію в органах влади, політичний лобізм, невміле планування й управління фінансовими ресурсами дотації практично вичерпали себе, про що свідчить зменшення в понад десять разів їх питомої ваги у структурі доходів місцевих бюджетів. Запропоновано заходи щодо послаблення трансфертної залежності місцевої влади і створення умов для свободи реалізації власної бюджетної політики. Письменный В. В. Дотации в обеспечении финансового потенциала територий.Проанализировано современное состояние и проблемы функционирования дотаций в доходах местных бюджетов Украины. Теоретически они являются достаточно эффективным методом бюджетного регулирования, позволяющим извлечь фиксированную сумму средств из бюджета высшего уровня для сбалансирования бюджета низше-го уровня в случае превышения расходов последнего над его доходами. Установлено, что в Украине из-за коррупции в органах власти, политического лоббизма, неумелого планирования и управления финансовыми ресурсами дотации практически исчерпали себя. Об этом свидетельствует уменьшение более чем в десять раз их доли в структуре доходов местных бюджетов. Предложены мероприятия по ослаблению трансфертной зависимости местной власти и созданию условий для реализации собственной бюджетной политики. Pysmennyi V. Grants in providing financial potential of territories.Introduction. Government grants are a very specific instrument in the functioning of local budgets. On the one hand, the high degree of liberalization of their use makes it possible for local authorities to channel financial resources to programmes and measures that, subjectively, are most needed for the economic and social development of territories. On the other hand, such liberalization poses a potential threat to the self-sufficiency of local budgets in Ukraine. Even with the formation of an open and civil society, such phenomena as corruption in the authorities, political lobbyism, inefficient planning and management of financial resources are still deeply engrained into the system of intergovernmental transfers.Purpose. Analysis of domestic experience of government grants in local budget revenues and justification of proposals to ensure their effectiveness.Methods. In the course of writing the article, several methods were used. Among them were the method of scientific abstraction and analogues, analysis, formal logic and dialectics.Results. It has been established that government grants, as an integral element of intergovernmental transfers in democratically-developed countries, are a fairly effective method of budget regulation. They allow you to remove a fixed amount of funds from a higher-level budget to balance the lower-level budget in case of excessive expenditure over income. It is substantiated that government grants exhausted themselves in Ukraine, as evidenced by a decrease of their share in the structure of local budget revenues by more than ten times. This is due to corruption in the authorities, political lobbying, inefficient planning and management of financial resources. While until 2014 government grants were used almost equally to subventions, today their fiscal role has much lessened.Conclusion. The decrease in government grants in the revenues of local budgets of Ukraine does not in any way suggest a reduction of the transfer dependence of local authorities. In addition, their cancellation is not considered as part of further reform of inter-budgetary relations. The general increase in the amount of financial assistance from the centre indicates a lacking motivation of local authorities to increase their own revenue base, and that paternalism has transformed into a budget “dependency”.